On transits and transitions : trans migrants and U.S. immigration law - Josephson, Tristan (Rutgers University Press, 2023)
Celebrations of the "transgender tipping point" in the second decade of the twenty-first century occurred at the same time of heightened debates and anxieties about immigration in the United States. On Transits and Transitions explores what the increased visibility of trans people in the public sphere means for trans migrants and provides a counter-narrative to the dominant discourse that the inclusion of transgender issues in law and policy represents the progression of legal equality for trans communities. Focusing on the intersection of immigration and trans rights, Josephson presents a careful and innovative examination of the processes by which the category of transgender is produced through and incorporated into the key areas of asylum law, marriage and immigration law, and immigration detention policies. Using mobility as a critical lens, On Transits and Transitions captures the insecurity and precarity created by U.S. immigration control and related processes of racialization to show how im/mobility conditions citizenship and national belonging for trans migrants in the United States.